New record for Peru of the invasive Asian beetle Xylopsocus capucinus (Fabricius, 1781) (Coleoptera: Bostrichidae: Bostrichinae), with biological and ecological notes - Chuquibala Checan, Beimer (2025)
As part of our study of saproxylic fauna in cocoa (Theobroma cacao Linnaeus, 1753) sites in northern Peru, we present a new record of Xylopsocus capucinus (Fabricius, 1781) in the country. The species X. capucinus is considered an invasive beetle in the Bostrichidae family to Central America. Our report includes biological and ecological data from this site, as well as detailed taxonomic information and images to facilitate identification.